THE IMPLEMENTATION OF ISO 9001: 2015 QUALITY MANAGEMENT SYSTEM AT PT TARUMATEX BANDUNG - Hernawan, Yosep; Kesuma Dewi, Sri Wijaya; Musafa, Musafa (Journal of Economicate Studies, 2018)
The application of ISO 9001: 2015 becomes an important issue in line with increasingly competitive competition in the industrial world. The company strives to maintain its position and increase consumer confidence. ISO 9001: 2015 can be used as a tool to measure the company's credibility globally and improve the quality of company management and meet the demand for products and services according to the wishes of consumers. The research aims to find out how far the application of ISO 9001: 2015 as a Quality Management System is applied in a company, what benefits will a company achieve when implementing an ISO 9001: 2015 Quality Management System, identify problems and solutions and what steps companies must take in order to implement the Management System ISO 9001: 2015 quality can run well. The approach used is a qualitative descriptive method. The results obtained in the form of a recapitulation of the implementation of ISO 9001: 2015 in the company in the form of constraints and obstacles, evaluation and benefits obtained after implementing the ISO 9001: 2015 Quality Management System such as the division of authority and responsibilities of each division that is clearer, communication and response faster towards customers, continuous improvement and so on.